Non-traditional small companion mammals in Spain as reservoirs of antimicrobial-resistant Staphylococci - Marco-Fuertes, Ana; Marin, Clara; Villora-Gonzalez, José; Gimeno-Cardona, Concepción; Artal-Muñoz, Violeta; Vega, Santiago; Montoro-Dasi, Laura (Frontiers in Veterinary Science, 2024)
The increasing prevalence of antimicrobial resistance (AMR) and multidrug resistance (MDR) in microorganisms poses a significant concern in both human and veterinary medicine. Non-traditional companion animals (NTCAs), particularly popular among households with children, play a crucial role in AMR epidemiology due to their rising population. Indeed, it is known that some of these animals may act as reservoirs of zoonotic pathogens and thus be able to spread and transmit them to family members, along with their AMR, through their shared environment. It is therefore imperative to address this concern with the involvement of human, animal and environmental health professionals. This pilot study aimed to assess the prevalence and AMR patterns of Staphylococcus spp. strains obtained from commensal mucosal and skin infection samples in NTC small mammals, with a focus on strains like methicillin-resistant Staphylococcus spp. (MRS) that are critical in public health. For this purpose, 81 animals of different small mammal species were sampled, assessing antimicrobial susceptibility to 26 relevant antimicrobial agents (AMAs) in human health using minimum inhibitory concentration assays, and interpreting them according to EUCAST and CLSI guidelines. The isolated Staphylococci strains were identified by MALDI-TOF, with the predominant species being Mammalicoccus sciuri and Staphylococcus aureus. Including all strains isolated, AMR was observed against all 26 AMAs, including six last-resort AMAs in human medicine. Additionally, over 85 % of the strains exhibited MDR. These findings underscore the need to monitor AMR and MDR trends in companion animals and emphasise the potential role of NTCAs in spreading resistance to humans, other animals, and their shared environment, calling for a comprehensive "One Health" approach.